2022
DOI: 10.1080/10494820.2021.2025405
|View full text |Cite
|
Sign up to set email alerts
|

A learning model for improving in-service teachers’ course completion in MOOCs

Abstract: The use of massive open online courses (MOOCs) for teacher professional development (TDP) has increased in the past decades. This study explored the key factors that influenced teachers' online course completion as a significant indicator of their success in a TPD MOOC. Participants' selfassessment of Technological Pedagogical Content Knowledge (TPACK), interaction with curriculum content and peers, satisfaction, and overall course score were identified as key influencing factors. Employing a learning model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
9
0
2
Order By: Relevance
“…Next, there is a positive relationship between interaction and a learner's motivation. It has been found that the interaction between learners can reduce loneliness and increase satisfaction, thus promoting the continuance intention (Ma et al, 2022). The interaction between instructors and learners directly affects a learner's motivation to complete the course (Khan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, there is a positive relationship between interaction and a learner's motivation. It has been found that the interaction between learners can reduce loneliness and increase satisfaction, thus promoting the continuance intention (Ma et al, 2022). The interaction between instructors and learners directly affects a learner's motivation to complete the course (Khan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Next, there is a positive relationship between interaction and a learner's motivation. It has been found that the interaction between learners can reduce loneliness and increase satisfaction, thus promoting the continuance intention (Ma et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Online PD has gained popularity over the past 2 decades (King, 2002;Powell & Bodur, 2019) with many universities offering the option of completing PD online (Al-Bargi, 2021;Mulla et al, 2020). However, access to online education does not guarantee active use of such learning resources or high-level learning engagement (Gibson et al, 2008;Ma et al, 2022). For online learning success, the priority needs to shift from ensuring online learning readiness to learners' actual acceptance and engagement (He et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the appeal of providing education with very flexible time and space boundaries, some real concerns about online learning exist. Many authors state that traditional MOOCs (Massive Open Online Courses) are not very effective due to the lack of student–teacher and student-to-student interaction; however, when opportunities for interaction and teacher responsiveness are added, the effectiveness can be improved significantly ( Ma et al, 2022 ). Moreover, previous research has shown that high interaction rates are positively associated with students’ intention to continue learning ( Fang et al, 2019 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%